The role of organizational culture on job satisfaction mediated by perceived organizational support in hospital employees - Aulia, Aulia; Husain, Ahmad Fauzan; Zahrotunnisa', Mutamimah; Charismatica, Mutiara; Bakhtiar, Rakhman (Jurnal Psikologi, 2025)
Background: The role of hospital employees occupies a crucial position in supporting healthcare services for patients, thereby necessitating attention to employee satisfaction. Previous research has reviewed factors related to job satisfaction. Purpose: This study aims to examine the influence of organizational culture on job satisfaction among hospital employees, with perceived organizational support as a mediating variable. Method: This research employs a quantitative approach with a cross-sectional study method. The population in this study consists of hospital employees. Participants in this study totaled 313 individuals, selected using purposive sampling technique. Data collection was conducted by adopting psychological measurement tools, namely job satisfaction scale, perceived organizational support scale, and organizational culture scale. Data analysis was performed using the Partial Least Square Structural Equation Modeling (PLS-SEM) technique with the help of SmartPLS 4 software. Findings: Hypothesis testing results in the structural model evaluation indicate that organizational culture affects job satisfaction through perceived organizational support as a mediator. Implication: Establishing a positive organizational culture and ensuring that employees feel supported in the workplace will help hospitals improve employee job satisfaction.